Evaluation on effect of particle size on mechanical properties of polymer composites based on epoxidized linseed oil reinforced by quartz and recycled glass particles - Tuan, Pham Anh; Dieu, Tran Vinh; Phuc, Bach Trong (Vietnam Journal of Chemistry, 2015)
Epoxidized linseed oil (ELO) was used to prepare green polymer composite materials (PC) reinforced by quartz particle and recycled glass. The surface structure of PC based on ELO was investigated by scanning electron microscopy (SEM). Furthermore, in this study, the preparation method of PC based on ELO was introduced and the results showed that with the increase in particle size the ELO resin content in PC material is decreased. The effect of particle size on the mechanical properties such as bending strength, impact strength, deep abrasion, water absorption and chemical resistance of PC was investigated. Keywords. Polymer composites, epoxidized linseed oil, artificial stone, SEM, mechanical properties.